2008
DOI: 10.1143/jjap.47.5167
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Glassy Carbon Molds Using Hydrogen Silsequioxane Patterned by Electron Beam Lithography as O2 Dry Etching Mask

Abstract: Glass is a good candidate material for optical devices because of its enhanced optical properties, the technique of die machining has not been established for the hot embossing of glass. In this study, we used the glassy carbon (GC) mold for the hot embossing of glass. An inductively coupled plasma reactive ion etching (ICP-RIE) using oxygen plasma was employed for the submicron structuring of the GC mold. Hydrogen silsesquioxane (HSQ) is a negative-type electron beam (EB) resist used to be resistant to oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
2
6
0
Order By: Relevance
“…The contact angles obtained at every measurement temperature are given in Table 2. The working temperature of glass mold press machines 6 and the imprinting temperature for borosilicate glass as reported by the authors 3, 4, 7 are close to 600 °C. Considering that the contact angle for electrodeposited Ni‐W alloy film was above 90 °C at 700 °C (about 100 °C higher than the imprint temperature), we may infer that this is a practicable mold material for B 2 O 3 ‐La 2 O 3 ‐based glass.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The contact angles obtained at every measurement temperature are given in Table 2. The working temperature of glass mold press machines 6 and the imprinting temperature for borosilicate glass as reported by the authors 3, 4, 7 are close to 600 °C. Considering that the contact angle for electrodeposited Ni‐W alloy film was above 90 °C at 700 °C (about 100 °C higher than the imprint temperature), we may infer that this is a practicable mold material for B 2 O 3 ‐La 2 O 3 ‐based glass.…”
Section: Resultssupporting
confidence: 55%
“…Hence, there is a need for research on imprint mold materials that can support the production of nonreflective structures on B 2 O 3 ‐La 2 O 3 ‐based glass. The authors have investigated electrodeposited Ni‐W alloy films 3 and glasslike carbon (GC) 4 as imprint mold materials for borosilicate glass. We found that both materials might be used as imprint molds for borosilicate glass at 600 °C.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that a microstructure on a Ni-W electrodeposited film obtained by a FIB can be used as a mold for glass press molding. 16) Additionally, we confirmed that the Ni-W electrodeposited film is a chemically stable material for borosilicate glass molding. 17) From these reports, we investigated the property variation of the Ni-W electroformed mold by micro-press molding.…”
Section: Introductionsupporting
confidence: 70%
“…The linear expansion coefficient of Incoloy909 is similar to that of borosilicate glass. 16) The Incoloy909 substrate was cleaned by a dilute hydrofluoric acid treatment. A Ni-W film with a thickness of 2 m was deposited on the Incoloy909 substrate with a current density of 1200 A/m 2 and a Ni-W solution temperature of 333 K. The plating time was 10 min [Fig.…”
Section: Fabrication Process Of the Ni-w Electroformed Moldmentioning
confidence: 99%
“…SiO 2 film is the hopeful material as a mask in RIE on SiC. The hydrogen silsesquioxane (HSQ : (HSiO 3/2 ) n ) can draw it by an electron beam [8] and can change to silica structure from HSQ (FOx14 @Dow Corning) by thermal annealing at 800 o C for 30 min in O 2 ambient. The dot pattern was formed out of electron beam drawing by EB Lithography System (Elionix Inc. ELS-6600C) with LaB 6 gun into a HSQ resist on the 4H-SiC (0001) 4 o off n-type epi-wafer.…”
Section: Methodsmentioning
confidence: 99%